Financial sustainability in UMP's strategic plan - Hazlina, Faizal (Penerbit UMP, 2012)
As a public institution of higher learning and federal statutory body, Universiti Malaysia Pahang (UMP) is responsible in helping the government to realize the aspiration of providing excellent services to its clients.